TPACK's Approach to Cultivating Creative Thinking Skills of V SD Class Students on Light Materials Properties - Dinda, Nausya Nurdinda Eka Saputri; Imas Srinana Wardani; Susi Hermin Rusminati (Universitas Negeri Semarang, 2024)
This research is hampered by a lack of creative thinking skills in V-grade students, although these skills are essential in preparing for educational success in today's growing era of globalization. This research aims to find out the influence of TPACK's approach in cultivating the creative thinking skills of students of V SD class on the material properties of light. The research uses quantitative research design, experimental Quasi design through non-equivalent pre-test and post-test control group design. The population of this study is the entire student SDN Buncitan Sedati Sidoarjo, the sample of the research used included students of the VA class (control class) which totalled 30 students and VB (experimental class) that totals 30 students. Data collection techniques use test techniques consisting of 10 creative thinking skills essays. The result of this study is a sig. (2-tailed) value of 0,000 < 0.05 which means H0 rejected and H1 accepted, which means there is an influence of the TPACK approach in cultivating the creative thinking skills of students of grade V SD on the material of light properties.